2017
DOI: 10.1002/jcb.26275
|View full text |Cite
|
Sign up to set email alerts
|

Effect of metformin on ossification and inflammation of fibroblasts in ankylosing spondylitis: An in vitro study

Abstract: Ankylosing spondylitis (AS) is an autoimmune disease characterized by fibroblasts ossification. However, effective drug therapy for AS is lacking. As an antidiabetic drug, metformin has demonstrated an antiosteogenic effect on osteoblasts in vitro. And it is also a kind of specific agonists for adenosine 5′-monophosphate activated protein kinase (AMPK), which is blocked in the process of AS. Given the role in antiosteogenesis and AMPK activating, metformin was investigated of its effect on fibroblasts harveste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 36 publications
1
34
0
Order By: Relevance
“…In cardiac fibroblasts, metformin treatment has been shown to inhibit fibrosis and collagen synthesis via the TGF-β/Smad3 signaling pathway ( 120 ) and to impair the differentiation into myofibroblasts ( 121 ). A similar effect was observed in other cellular models, including nasal polyp-derived fibroblasts ( 122 ), renal fibroblasts ( 123 ), hepatic stellate cells ( 124 ), and in fibroblasts harvested from capsular ligaments of ankylosing spondylitis patients ( 125 ). In lungs, metformin attenuates gefitinib-induced exacerbation of pulmonary fibrosis by inhibiting the TGF-β/SMAD2/3 signaling pathway ( 126 ).…”
Section: Effects Of Metformin On Other Cells Involved In Autoimmune Dsupporting
confidence: 73%
“…In cardiac fibroblasts, metformin treatment has been shown to inhibit fibrosis and collagen synthesis via the TGF-β/Smad3 signaling pathway ( 120 ) and to impair the differentiation into myofibroblasts ( 121 ). A similar effect was observed in other cellular models, including nasal polyp-derived fibroblasts ( 122 ), renal fibroblasts ( 123 ), hepatic stellate cells ( 124 ), and in fibroblasts harvested from capsular ligaments of ankylosing spondylitis patients ( 125 ). In lungs, metformin attenuates gefitinib-induced exacerbation of pulmonary fibrosis by inhibiting the TGF-β/SMAD2/3 signaling pathway ( 126 ).…”
Section: Effects Of Metformin On Other Cells Involved In Autoimmune Dsupporting
confidence: 73%
“…Previous studies have demonstrated the involvement of BMP signaling pathway in new bone formation in AS [ 34 ]. The PI3K–Akt signaling pathway and its downstream targets were reported to be critical regulators of bone formation and involved in the pathogenesis of AS [ 35 ]. The JAK–STAT signaling pathway has also been suggested to regulate Th17 cells in AS [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…These lncRNAs were also associated with signaling pathways including the TNF, PI3K-Akt, Rap1, Hippo, and HIF-1 pathways, which are primarily involved in in ammatory immune regulation and osteogenic differentiation. In some prior studies, the PI3K-Akt signaling pathway has been suggested to promote broblastic ossi cation and in ammation in the context of AS [24]. Some of the identi ed pathways, including the Rap1, Hippo, and HIF-1 pathways, have not previously been studied in the context of AS, and thus warrant future investigation.…”
Section: Discussionmentioning
confidence: 98%